The Relationships Between Stasys Lozoraitis and the Chief Committee for Lithuania’s Liberation in 1947–1948 - Jonušauskas, Laurynas (Genocidas ir rezistencija, 1998)
A long history of the relations between the chief of diplomacy Stasys Lozoraitis and the Supreme Committee for the Liberation of Lithuania (VLIK) had a unique place in the political consciousness of the Lithuanian emigration. These were two parallel political lines that were moving in the same direction, but which did not agree with each other in principle. The chief of the Lithuanian diplomacy, Stasys Lozoraitis, and the VLIK and their relations were the axis around which almost the entire Lithuanian political diaspora living in Europe in the 1940s–1950s revolved.